2018
DOI: 10.1111/anu.12822
|View full text |Cite
|
Sign up to set email alerts
|

Progress in diet development for blue swimmer crab,Portunus pelagicus, juveniles: Effect of dietary phospholipid on survival, development, growth and resistance to osmotic shock

Abstract: This study examined the effects of dietary phospholipid (PL) level on survival, growth, development and resistance to osmotic shock of early blue swimmer crab, Portunus pelagicus, juveniles. Six iso‐lipidic diets formulated to contain PL at 0 (basal), 30, 60, 90, 120 and 150 g/kg (dry matter) were offered to first‐stage crabs (C1) until they achieved C4 stage. Highest survival (93.3%) was achieved by crabs fed diets with PL supplementation levels of 120 and 150 g/kg. Crabs fed diets with PL supplementation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Mankura, Dalimunthe, and Kayama () compared the level of cholesterol esterification in crustaceans, fish, rats, and human beings and suggested that crustaceans had the lowest lecithin: cholesterol acyltransferase activity, which is responsible for cellular cholesterol metabolism, particularly cholesterol contained in plasma lipoproteins. In a previous study with P. pelagicus juveniles of a size similar to those used here, dietary phospholipid (PL) supplementation was reported to markedly improved their growth, and optimal growth was achieved when the crabs were fed diets containing a PL level of >79 g/kg PL (Noordin et al, ). However, in the present study, all experimental diets contained lower levels of phospholipid at 60 g/kg dry diet.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Mankura, Dalimunthe, and Kayama () compared the level of cholesterol esterification in crustaceans, fish, rats, and human beings and suggested that crustaceans had the lowest lecithin: cholesterol acyltransferase activity, which is responsible for cellular cholesterol metabolism, particularly cholesterol contained in plasma lipoproteins. In a previous study with P. pelagicus juveniles of a size similar to those used here, dietary phospholipid (PL) supplementation was reported to markedly improved their growth, and optimal growth was achieved when the crabs were fed diets containing a PL level of >79 g/kg PL (Noordin et al, ). However, in the present study, all experimental diets contained lower levels of phospholipid at 60 g/kg dry diet.…”
Section: Discussionmentioning
confidence: 77%
“…Thirty healthy C1 crabs with a mean dry weight of 0.57 ± 0.03 mg and mean carapace length and carapace width of 2.34 ± 0.02 and 2.87 ± 0.05 mm, respectively, were used for each diet treatment, and each culture unit was regarded as a replicate; hence, a total of 210 crabs were used for the experiment. The individual housing of all P. pelagicus juveniles eliminated the compounding effects of cannibalism and allowed precise recording of consecutive intermolt periods for each crab (Noordin et al, ). The culture units were randomly placed within a water bath to maintain the water temperature within the culture units at 28 ± 2°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turbot, it reduced the hepatic lipid content, plasma triglyceride concentration, and total cholesterol level and increased the plasma free fatty acid contents as well [ 19 ]. However, the lysophospholipid synthesis in fish is usually insufficient to meet their metabolic requirements [ 20 , 21 ]. Diets supplemented with exogenous lysophospholipid could improve protein efficiency ratio and growth of rainbow trout ( Oncorhynchus mykiss ) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%